Intumescent coatings, ultra-long term durability, and sustainable fire protection solutions - Burrell, Carl (2022)
ABSTRACT: Modern, sustainable construction requires building materials and products used to be fit for long term durability and in-service resilience. Intumescent coatings for fire protection of steel have been in use for over 30 years, providing excellent protection against the effects of fire. However, the weather resistance of some types of intumescent coating can be limited. This paper considers long term durability of a novel technology in this field and will show that correct specification of products can provide fire protection to buildings and structures for the entire design life, and possibly beyond.